Exploring the Relationship Between Professional Identity and Psychological Resilience of Organ Donation Coordinators in Zhejiang Province (China) - Shu, Wan; Xing, Bing-yu; Ruan, Wei-xiu; Gao, Li-yan; Miao, Qun-fang (Frontiers in Public Health, 2021)
Background: An organ donation coordinator plays an important role in the process of organ donation and transplant. Therefore, investigating and analyzing the current situation in organ donation and examining the correlation between professional identity and psychological resilience of human organ donation coordinator, provides a reference for promoting stable development of organ donation. Methods: A total of 48 coordinators of organ donation in Zhejiang Province were recruited for the study by using the method of convenience sampling. The psychological resilience scale and professional identity questionnaire were used to collect data. Results: The results revealed that the total average score of the professional identity of organ donation coordinators was 34.92 ± 8.57. Compared with the median professional identity score of 34.50, the professional identity of the coordinator in this survey was at a moderate level. The total average score of psychological resilience was 64.44 ± 11.91. There was a significant positive correlation between the professional identity of the coordinator and the total score of psychological resilience (r = 0.641, P < 0.01). Conclusion: The professional identity and psychological resilience of the coordinators in Zhejiang Province were found to be in the middle level and the higher the psychological resilience score, the stronger the professional identity of the coordinators. It is important to improve the level of psychological resilience among organ donation coordinators to enhance their professional identity.